Mapping of Natural Frequency, Amplification, Seismic Vulnerability, and Vs30 Velocity in Selebar District, Bengkulu City - Samuel Siagian; Refrizon; Arif Ismul Hadi (Universitas Negeri Semarang, 2025)
Research using the microtremor method has been conducted in Selebar District, Bengkulu City, to estimate the ground response to earthquake vibrations. The purpose of this research is to support building mitigation in earthquake-prone areas. Microzonation mapping is conducted by analyzing the dominant frequency (f0), amplification factor (A0), seismic vulnerability (Kg), and shear wave velocity (Vs30). The Horizontal to Vertical Spectral Ratio (HVSR) method is used in microtremor analysis. The results show the dominant frequencies consist of 40.8% hard gravelly sandstone, 26.5% alluvial rock with a thickness of 5 meters, 18.4% alluvial rock with bluff formation and 14.3% delta sediments. The amplification values include 40.8% in the low category, 56.1% in the medium category and 3.1% in the high category. The seismic vulnerability index indicates that 63.3% is below 3 level, 26.5% is between 3-6 level and 10.2% is between 6-9 level. The shear wave velocity (Vs30) values show that 8.2% is above 1500 m/s, 10.2% is between 750 m/s and 1500 m/s, 55.1% is between 350 m/s and 750 m/s, 25.5% is between 175 m/s and 350 m/s, and 1.1% is below 175 m/s. In conclusion, Selebar District has hard rock layers and low seismic vulnerability, rendering it generally safe from earthquakes.